India's South-South Cooperation in Human Resource Development. Issue 4 (4th July 2019) - King, Kenneth; King, Pravina
ABSTRACT: The article reviews several of the main modalities of India's human resources' involvement with other developing economies, and especially those in Africa. These involve the provision of long-term scholarships and short-term professional training awards. Comparison is made, in the case of international students, between the scholarship and privately funded categories, and also between those from Commonwealth and non-Commonwealth countries. Comparable data on such assisted foreign student flows are also offered in respect of South Africa. Other modalities of India's HRD engagement with Africa are analysed, including those associated with the India-African Forum Summits (IAFS). India also does capacity building through non-state actors, notably nongovernment organisations and the private sector. Furthermore, it promotes cultural diplomacy through its Indian Cultural Centres and Chairs of Indian Studies, though these are not restricted to developing economies. Although attention is paid to the Commonwealth dimension in these comparisons, it is acknowledged that the classification of students and countries as Commonwealth may not be as widespread or meaningful today as 60 years ago.